2020
DOI: 10.1177/0964528420920307
|View full text |Cite
|
Sign up to set email alerts
|

A Malaysian retrospective study of acupuncture-assisted anesthesia in breast lump excision

Abstract: Introduction The objective of this retrospective study was to evaluate the effectiveness and safety of acupuncture-assisted anesthesia (AAA) in breast lump excision. Methods The medical records of all patients who underwent breast lump excision under AAA in combination with electrical stimulation at traditional acupuncture points in 2016 were examined. All of them (n = 17) received electrostimulation (2–4 Hz) using single needles inserted at bilateral LI4 and PC6. They also underwent insertion of four acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…During this period, severe hemodynamic abnormalities, severe stress response, obvious postoperative anesthesia side effects and high incidence of adverse reactions easily occur ( 7 , 8 ). Therefore, how to minimize the use of anesthetics and avoid the occurrence of postoperative adverse conditions when ensuring the anesthesia effect is a difficult problem to be solved in general anesthesia surgery for clinical elderly patients ( 9 , 10 ). Acupuncture analgesia has recently been a hot topic of academic research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, severe hemodynamic abnormalities, severe stress response, obvious postoperative anesthesia side effects and high incidence of adverse reactions easily occur ( 7 , 8 ). Therefore, how to minimize the use of anesthetics and avoid the occurrence of postoperative adverse conditions when ensuring the anesthesia effect is a difficult problem to be solved in general anesthesia surgery for clinical elderly patients ( 9 , 10 ). Acupuncture analgesia has recently been a hot topic of academic research.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with conventional acupuncture, EA is more effective and convenient, so EA is often used to assist anesthesia and analgesia in various surgical procedures. ( 10 , 11 ). It has been reported that in a variety of local anesthesia surgerys, EA can significantly enhance the perioperative analgesic effect, improve hemodynamic abnormalities, and reduce the incidence of adverse reactions after anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The acupuncture protocol is based on previous clinical studies and case reports of acupuncture anaesthesia 9 16. During the ablation procedure, the patients will be placed in the supine position and will be asked to expose their left upper arm and wear an eye mask.…”
Section: Methodsmentioning
confidence: 99%
“…8 AAA is generally considered safe, with only mild adverse events (AEs), including haematoma, bleeding and pain. 9 It is an important part of multimodal non-opioid analgesia and has been applied to parturition, surgery and minimally invasive procedures. 10 11 Such analgesic effects might be mediated by encephalin and endorphin following the use of AAA with electrical stimulation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation